Hubungan Pengetahuan Perawat Dalam Menjalankan SOP Pemberian Obat High Alert Dengan Kejadian Medication Error - Arisma, Degi; Muharni, Sri; Wardhani, Utari Christya (REAL in Nursing Journal, 2023)
Background: Patient safety is now a global issue due to the large number of reports regarding claims for medical errors that occur to patients. This research aims to determine the relationship between nurses' knowledge in implementing the SOP for administering high alert medications and the incidence of medication errors at Raja Ahmad Tabib Regional Hospital. Methods: This type of research is quantitative descriptive with a cross-sectional approach. The sampling method was a total sampling of 103 respondents. Data collection methods and tools used a questionnaire with 16 statement items related to standards for administering High Alert medication. Data analysis was carried out using the chi-square test. Results: The results of research using univariate analysis show that the level of knowledge of nurses in carrying out SOPs for administering high alert medications is in the high category, namely 94.2% and for medication error incidents with a percentage of 1%. Bivariate analysis showed significant results on nurses' knowledge in carrying out standard operational procedures for administering high alert medications with the incidence of medication errors being 0.000 (< 0.05). Conclusion: It was concluded that there was a significant relationship between nurses' knowledge in carrying out standard operational procedures for administering high alert medications and the incidence of medication errors at Raja Ahmad Tabib Hospital, Riau Islands Province. It is recommended for nurses to be disciplined in carrying out standard operational procedures for administering high alert medications so as to minimize the incidence of medication errors and as a form of accountability in nursing professional ethics.Keywords: Knowledge, Standard Operating Procedure, Medication Error